PERTUMBUHAN SEMAI JATI (Tectona grandis L.f) PADA APLIKASI BERBAGAI KONSENTRASI HORMON GIBERELIN DI PERSEMAIAN - Adilah, Nur; y, Yusran; Taiyeb, Asgar (Universitas Tadulako, 2019)
The problems that are still faced at this time include the lack of enviromentally sound cultivation technology to support teak growth rates quickly and efficiently. One of the efforts to overcome this problem is to use a Gyberelin (GA3) growth regulator, which isknown to accelerate plant growth, so that dwarf plants can grow taller in a relatively short time. The research aims to determine the effect of various concentration s of administration of Gyberelin (GA3) grawth regulators on teak seedlings (Tectona grandis L.f) in nurseries. This research uses a completely randomized design method consisting of four treatments, namely G0= (Control), G1= 100 ppm, G2= 200 ppm, G3= 300 ppm. The results of the research showed that the addition of various concentrations of Gyberelin hormone in the nursery had a significant effect o the height increase and increase in the number of teak seedling leaves, but it did not signficantly affect the diameter of teak seedlings. Treatment of Gyberelin (GA3) with a concentration of 300 ppm (G3) gave the best influence on teak growth in terms of height increase and number of leves compared to control treatment (G0), as well as concentration 0f 100 ppm (G1) and 200 ppm (G2).